Chlordecone potentiates auto-immune hepatitis and promotes brain entry of MHV3 during viral hepatitis in mouse models. (15th December 2018) - Tabet, Elise; Gelu-Simeon, Moana; Genet, Valentine; Lamontagne, Lucie; Piquet-Pellorce, Claire; Samson, Michel
Highlights: Chlordecone potentiates auto-immune hepatitis in mouse model. Chlordecone promotes brain entry of murine hepatitis virus type 3 in mouse model of viral hepatitis. Chlordecone impacts immunity in liver. Abstract: Chlordecone is an organochlorine used in the 1970's as a pesticide in banana plantations. It has a long half-life in the soil and can potentially contaminate humans and animals through food. Chlordecone targets, and mainly accumulates in, the liver, leading to hepatomegaly and neurological signs in mammals. Chlordecone does not cause liver injuries or any inflammation by itself at low doses, but it can potentiate the hepatotoxic effects of other chemicals and drugs. We studied the impact of chlordecone on the progression of acute hepatitis in mouse models of co-exposure to chlordecone with Concanavalin A or murine hepatitis virus type 3. We examined the progression of these two types of hepatitis by measuring hepatic transaminase levels in the serum and inflammatory cells in the liver, liver histological studies. Amplified tremors presented in the MHV3- chlordecone mouse model had led us to study the expression of specific genes in the brain. We show that chlordecone amplifies the auto-immune hepatitis induced by Concanavalin A by increasing the number of liver NKT cells, which are involved in liver damage. Chlordecone also accelerated the death of mice infected by murine hepatitis virus and enhanced the entry of the virus into the cervical spinal cord in infected mice, leading to considerable neurological damage. In conclusion, chlordecone potentiates both the Concanavalin A-induced hepatitis and brain damage caused by an hepatotropic/neurotropic virus.